PEMETAAN PERGERAKAN PENGGUNA LAYANAN KERETA COMMUTER JABODETABEK (PT.KCJ) MENGGUNAKAN SIMULASI - Pudji Astuti; Amal Witonohadi (JURNAL TEKNIK INDUSTRI, 2013)
Commuter Rail Line is one of the mean of public transportation in Jakarta andsurrounding areas. Passenger distribution maps (origin and destination passengers ) isrequired as a basis for policy formulation PT.KCJ to increase capacity in accordance withthe targeted services in the amount of 1.2 million passengers per day. Payload capabilitycurrently only 440,000 passengers per day. The purpose of this study is to design asimulation model mapping the movement of passengers . Method to determine the patternof passenger movement in each station using simulated data promodel.Input simulation aretime arrive , trains departure time, travel time between stations , the number of tap -in andtap- out . In the current study focused on the Bogor - Jakarta Kota during peak hour was at6:09 pm departure from Bogor. Simulation results show that number of passengers whoare most tap -in Bogor until Pasar Minggu , and the number of passengers who did mosttap - out begins from Manggarai until to Jakarta Kota .